Developing an interprofessional identity complementary to a professional identity - findings related to Extended Professional Identity Theory (EPIT) - Reinders, Jan Jaap; Başer Kolcu, Mukadder İnci; Kolcu, Giray (Frontiers in Medicine, 2024)
Collaboration among various professions often faces barriers owing to divergent perspectives, priorities, and expertise shaped by distinct socialization processes. These differences can hinder effectiveness, efficiency, and workforce well-being. The Extended Professional Identity Theory (EPIT) addresses this issue by fostering an interprofessional identity without weakening professional identities. Drawing from psychological theories, EPIT explains the coexistence of interprofessional and professional identities, and predicts associated behaviors. It also emphasizes the importance of combining interprofessional identity formation with developing interprofessional competencies and adapting to environmental factors to achieve synergy in (temporary or permanent) mixed profession groups. Introduced in 2018, EPIT research initially relied on the measurement of congruent interprofessional behaviors as indirect indicators of interprofessional identity that could not yet be measured. An experiment demonstrated that enhancing social identification in mixed profession groups with interprofessional assignments reduced the social hierarchy within six hours across three meetings. The 2020 development of the Extended Professional Identity Scale (EPIS) confirmed interprofessional identity as a three-dimensional social construct. So far, several scientific studies have supported many propositions of EPIT. These propositions are related to dimensionality and various psychometric properties, cross-cultural similarities, evidence and clues for interprofessional identity formation, and its predictive validity in interprofessional education and collaborative practice. Türkiye is among several countries (e.g., the Netherlands, Belgium, Germany, Lithuania, Finland, and Indonesia) where EPIT-based interprofessional identity is being investigated. To illustrate contextual differences and their potential cross-cultural implications, it is valuable to explore how interprofessional identity adds value in the Turkish context. This approach facilitates understanding the regional implications of interprofessional identity, including interprofessional education initiatives, increased university engagement, the development of measurement instruments, challenges and future directions, and national and international collaborations. This paper aims to explain and clarify EPIT propositions compared to other theories, describe current evidence, and outline future research directions, with a focus on developments within the Turkish context as a showcase.